Evaluation of an innovative logistics system based on the logistics efficiency index - Ismaуilov, Vilayat; Karpenko, Andrii (Management and Entrepreneurship: Trends of Development, 2024)
The innovation process is characterized by the process of converting scientific knowledge into innovation. The expansion of innovation processes is associated with the development of a national innovation system, which is based on the interaction of organizations (structures) of various forms of ownership that are engaged in the production of scientific knowledge and technologies (intellectual property objects) and their preparation for commercialization within national borders. The innovation process is cyclical and this process is carried out in stages. The article deciphers seven stages of the innovation process and notes that in the modern world, including Azerbaijan there is a need to switch to a strategy for innovative logistics development, which is becoming a global problem in this area. The development of innovative logistics technologies makes it possible to process large amounts of data and expand the prospects for using information and analytical centers of logistics providers.The article also provides classification features, types of logistic innovations and synthesis of basic and innovative logistics. It is determined that basic and innovative logistics primarily complement each other, but at the same time there is a contradiction between them. Only the optimal solution of the entire complex of mutual management tasks allows you to achieve your goals, since only the logistics system is able to recoup all logistical costs and ensure the highest efficiency. The issues related to the expediency of using innovative logistics are noted.The World Bank Logistics Efficiency Index is a unique benchmarking tool that measures the convenience of logistics systems in more than 140 countries with data for 2023. The index consists of six components - customs assessment, infrastructure assessment, ease of transportation assessment, quality assessment of logistics services, timeliness assessment and tracking.In market conditions, for the Post-Soviet countries, including the Transcaucasian countries, the strategic guideline for innovative development is the creation of a national innovation system, which this system will ensure the identification of innovation priorities, the formation and implementation of state programs, the development of innovative logistics and the stimulation of innovative activities. JEL Classification: M11, L81, L91, Q5, Q55